Redescription of Aduncothrips asiaticus (Ramakrishna and Margabandhu) (Thysanoptera: Aeolothripidae) with first description of the male. (2nd July 2020) - Rajan Remani, Rachana; Badagi, Rachana; Rayar, Shashikant Gurappa
ABSTRACT: The female of Aduncothrips asiaticus (Thysanoptera: Terebrantia: Aeolothripidae) is redescribed with illustrations based on specimens collected on an agriculturally important new host plant, Moringa oleifera Lam. The previously unknown male is also described.